Language And Logic In German Post-Hegelian Philosophy - Volker Peckhaus (Baltic International Yearbook of Cognition, Logic and Communication, 2008)
The German debates concerning the need for a reform of logic in post-Hegelian times took place under the label “The logical question”, a label introduced by Friedrich Adolf Trendelenburg. The main objective of these debates was to overcome the Hegelian identification of logic and metaphysics without re-establishing the old Aristotelian-scholastic formal logic. This paper presents the positions developed by Friedrich Adolf Trendelenburg, Otto Friedrich Gruppe, and Carl v. Prantl, each of whom advocated the importance of language in logic in order to introduce a more dynamical element into the alleged static character of formal logic.
Keywords: philosophy; analytic philosophy; history of philosophy